PENDEKATAN TERHADAP KEBIJAKAN NON PENAL DALAM PENANGGULANGAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH APARATUR PEJABAT PEMERINTAHAN DAERAH - Tiami, Wan Qatrunnada; Rahmadan, Davit; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Since the enactment of Law Number 31 of 1999 concerning the Eradication of Criminal Acts of Corruption and the amendment to Law Number 21 of 2001 concerning the Eradication of Criminal Acts of Corruption, it has not yet reached the point of success expected in Indonesia. This itself uses a penal policy (criminal law policy), but the penal policy is not effective in eradicating corruption, therefore other policies are needed, namely non-penal policies (policies outside of criminal law) in eradicating corruption.This research will be structured using normative juridical research, namely research that is focused on examining the application of rules or norms in positive law. The approach used in this research is to use a normative approach that is using the principle of legality. Data sources are supported by primary data sources, secondary data, and tertiary data. The data collection technique used is literature review. After the data is collected, it is analyzed qualitatively, and draws conclusions using the deductive method of thinking, namely analyzing the problem from a general form to a special form.Keywords: Corruption-Policy-Nonpenal